TREN PENGEMBANGAN KOMPETENSI KARYAWAN DALAM ERA DIGITAL: TINJAUAN LITERATUR SISTEMATIS - Nauli, Harum; Nauli, Kembang; Suriyani Sinaga, Irma; Nauli, Mawar; Sitompul, Pandapotan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Digital transformation has driven organizations to invest in employee competency development to face technological disruption and dynamic market demands. This study is a systematic literature observation analyzed using the SCISCAPE (Search, Cluster, Integrate, Critically Analyze, Synthesize, Present, Enhance Insight, Evaluate) approach. Literature from 2015–2024 was collected from academic databases such as Scopus, Google Scholar, and ScienceDirect, with keywords such as employee competency development, digital skills enhancement, and digital transformation training. The findings show that training methods such as e-learning, microlearning, and gamification are the main trends in digital competency development. The study also highlights the positive impact of training on organizational performance, despite obstacles such as weakening technology and low ROI evaluation. Practical implications include the need for data-driven adaptive training design, as well as the development of a national digital competency framework. This study contributes to formulating HR strategies that are relevant to the digital era and opens up space for more measurable further research.